Case of foreign body as a broom handle in the rectum - Lal, Vikash; Narayan, Pranav; Mahapatra, B.; Deolekar, S.; Patil, Vivek; Panchal, A. (International Journal of Research in Medical Sciences, 2017)
A 68 yrs old male patient with a foreign body (broom handle cover 11’inch) introduced as sexual perversion presented with lower abdominal pain, the management emphasis is a transanally retrieval and ruling out of rectal and colonic perforation under colonoscopy guidance under local anesthesia in pad.